The Effectiveness of Sociodrama to Improve Students’ Anger Management Skills - Awaliyah, Iyum Tsamratul Ainil; Taufiq, Agus; Hafina, Anne (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2019)
The school students still show aggressive behavior such as shouting, swearing and glaring when offended, mocking, kicking and fighting, all of these are because of the uncontrolled anger. The purpose of this study was to examine the effectiveness of sociodrama within psychoeducational group to improve anger management skills for class XI students of State Madrasah Aliyah 3 Majalengka. A quasi-experimental method with 30 participants of class XI State Madrasah Aliyah 3 Majalengka were administered. The random sampling technique was used in this study. The results of 40 items test for anger management skills scale obtained 30 items are valid (α = 0.90). Data analysis to determine the effectiveness of the sociodrama to improve anger management skills through Wilcoxon test. The results showed the skills to manage anger of students generally in the medium category, it means that students already have the skills to manage anger but it is not yet been consistent, therefore, sometimes students showed aggressive behavior and sociodrama technique within psychoeducational group is effective to improve students anger management skills.